Peking Prognostic Score, Based on Preoperative Sarcopenia Status, Is a Novel Prognostic Factor in Patients With Gastric Cancer - Xiong, Jianping; Hu, Haitao; Kang, Wenzhe; Li, Yang; Jin, Peng; Shao, Xinxin; Li, Weikun; Tian, Yantao (Frontiers in Nutrition, 2022)
Background: The present work focused on assessing the role of Peking prognostic score (PPS), a novel prognostic index based on muscle atrophy and lymphocyte-to-C-reactive protein ratio, within gastric cancer patient prognosis. Methods: We analyzed data collected from 774 gastric cancer cases between April 2011 to February 2016 (discovery cohort). The results were assessed in 575 gastric cancer cases from March 2016 to September 2019 (validation cohort). For evaluating skeletal muscle mass, we obtained computed tomography images at the third lumbar vertebra level (L3). We performed time-dependent receiver operating characteristic curve (t-ROC) to analyze PPS’s prognostic significance with others. Results: The discovery cohort enrolled altogether 774 patients with non-metastatic gastric cancer, including 639 (82.5%) males along with 135 (17.5%) females. The patients were divided into 3 groups. 166 patients (21.4%) were assigned into group 0, 472 (60.9%) in group 1, and 136 (17.7%) in group 2, respectively. An increased PPS was in direct proportion to an elder age, reduced body mass index, higher pTNM stage, perineural invasion and vascular invasion. We identified PPS to independently estimate patient overall survival (OS) together with disease-free survival (DFS) (both P < 0.001). Additionally, as revealed by t-ROC analysis, PPS exhibited the highest sensitivity compared with other prognostic scoring systems in predicting patient survival. Finally, we evaluated the prognostic value of PPS in the validation cohort, and confirmed that preoperative PPS to independently estimate patient OS and DFS. Conclusions: PPS accounts for an efficient nutrition-inflammation prognostic scoring system in gastric cancer patients.